Associations of varicose veins with cerebrospinal fluid biomarkers of Alzheimer’s disease pathologies in adults without dementia: the CABLE study - Liu, Min; Ma, Li-Yun; Li, Qiong-Yao; Huang, Liang-Yu; Hu, He-Ying; Tan, Lan; Hu, Hao (Frontiers in Aging Neuroscience, 2025)
BackgroundPrevious studies have found a correlation between varicose veins (VVs) and cognitive decline, and individuals with VVs have a higher prevalence of Alzheimer’s disease (AD). However, the associations between VVs and the core pathologies of AD have not yet been investigated. The research was designed to analyze the relationships between VVs and cerebrospinal fluid (CSF) biomarkers of AD pathologies.MethodsWe included 1,298 participants from the Chinese Alzheimer’s Biomarker and LifestylE (CABLE) database without dementia. Multiple linear regression (MLR) model was applied to assess the relationships between the VVs and CSF AD biomarkers. Then, we conducted subgroup analyses according to age, gender, education levels and apolipoprotein E genotype ε4 (APOE-ε4) carrier status. Additionally, mediation effects were assessed using causal mediation analyses with 10,000 bootstrapped iterations.ResultsIn total subjects, VVs had negative correlations with CSF Aβ42 (β = −0.157, p = 0.038) and CSF Aβ42/Aβ40 ratio (β = −0.272, p < 0.001), as well as positive correlations with CSF Aβ40 (β = 0.170, p = 0.024), CSF p-tau (β = 0.192, p = 0.008), CSF t-tau/Aβ42 ratio (β = 0.190, p = 0.011), and CSF p-tau/Aβ42 ratio (β = 0.248, p = 0.001), after adjusting for age, sex, education levels and APOE-ε4 carrier status. Subgroup analyses demonstrated that the relations between VVs and CSF AD biomarkers were more significant in female, mid-life adults (40–65 years), less-educated individuals and APOE-ε4 non-carriers. Moreover, CSF Aβ42/Aβ40 ratio might be a partial mediator of the association between VVs and p-tau pathology.ConclusionOur study found correlations between VVs and CSF AD biomarkers, suggesting that VVs may be a potential risk factor for the development of AD.